ВЕЙВЛЕТ–АНАЛИЗ АКТИВНОСТИ СИСТЕМЫ "ЯДРО-ДЖЕТ" КВАЗАРОВ И БЛАЗАРОВ В САНТИМЕТРОВОМ ДИАПАЗОНЕ - Рябов, М. И.; Сухарев, А. Л.; Вольвач, А. Е.; Вольвач, Л. Н.; Сыч, Р. А.; Аллер, М. (Одеські астрономічні публікації, 2011)
Long monitoring of fluxes of a radio emission blazars on centimetric and millimetric waves to be carring out since 1965 on РТ-26 the Radioastronomical observatory of Michigan university (UMRAO) in the USA (4.8, 8 and 14.5 Ggts) and since 1980 on РТ-22 scientific research institute «Crimean astrophysical observatory» (22 and 36.8 Ggts). Carrying out of the comparative analysis of application of a standard method a Fourier of the analysis and more modern weivlet analysis for detection of dynamics of changes of flows actively investigated four blazars was the purpose of the given activity: 3С120, 3С345, 3С446 and BL Lac.